FKBP9 promotes the malignant behavior of glioblastoma cells and confers resistance to endoplasmic reticulum stress inducers - Xu, Huizhe (J Exp Clin Cancer Res, 2020)
BACKGROUND: FK506-binding protein 9 (FKBP9) is amplified in high-grade gliomas (HGGs). However, the roles and mechanism(s) of FKBP9 in glioma are unknown. METHODS: The expression of FKBP9 in clinical glioma tissues was detected by immunohistochemistry (IHC). The correlation between FKBP9 expression levels and the clinical prognosis of glioma patients was examined by bioinformatic analysis. Glioblastoma (GBM) cell lines stably depleted of FKBP9 were established using lentiviruses expressing shRNAs against FKBP9. The effects of FKBP9 on GBM cells were determined by cell-based analyses, including anchorage-independent growth, spheroid formation, transwell invasion assay, confocal microscopy, immunoblot (IB) and coimmunoprecipitation assays. In vivo tumor growth was determined in both chick chorioallantoic membrane (CAM) and mouse xenograft models. RESULTS: High FKBP9 expression correlated with poor prognosis in glioma patients. Knockdown of FKBP9 markedly suppressed the malignant phenotype of GBM cells in vitro and inhibited tumor growth in vivo. Mechanistically, FKBP9 expression induced the activation of p38MAPK signaling via ASK1. Furthermore, ASK1-p38 signaling contributed to the FKBP9-mediated effects on GBM cell clonogenic growth. In addition, depletion of FKBP9 activated the IRE1α-XBP1 pathway, which played a role in the FKBP9-mediated oncogenic effects. Importantly, FKBP9 expression conferred GBM cell resistance to endoplasmic reticulum (ER) stress inducers that caused FKBP9 ubiquitination and degradation. CONCLUSIONS: Our findings suggest an oncogenic role for FKBP9 in GBM and reveal FKBP9 as a novel mediator in the IRE1α-XBP1 pathway.